Synthesis and electrochemical performance of ZnCo2O4 for lithium-ion battery application. (10th February 2015) - Wang, Wei; Yang, Yun; Yang, Shuijin; Guo, Zaiping; Feng, Chuanqi; Tang, Xingchun
Abstract: ZnCo2 O4 was synthesized through the rheological phase reaction method using zinc acetate dehydrate, cobalt (II) acetate tetrahydrate, and citric acid as raw materials. The precursors were heat-treated in a muffle furnace at 400 °C or 500 °C, respectively. The samples were characterized by X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. The electrochemical properties of the samples were investigated. The results show that ZnCo2 O4 nanoparticles were synthesized successfully. The particles took on irregular quasi-spherical shapes, and the sizes of the particles were less than 100 nm. The electrochemical properties showed that the ZnCo2 O4 synthesized at 400 °C featured better reversible capacity than that of ZnCo2 O4 synthesized at 500 °C, and its specific capacity was 801 mAh g −1 after 100 cycles at a constant current of 100 mAh g −1 in the voltage range of 0.01–3 V. Hence, the ZnCo2 O4 synthesized by this method could be a promising anode material for lithium ion battery application.